Informing effective smokefree policies in Argentina: air quality monitoring study in 15 cities (2007-2009) Políticas efectivas de ambientes libres de humo de tabaco en Argentina: estudio de monitoreo de calidad del aire en 15 ciudades (2007-2009) - Verónica Schoj; Ernesto M Sebrié; María Elizabeth Pizarro; Andrew Hyland; Mark J Travers (Instituto Nacional de Salud Pública, 2010)
Objective. To evaluate indoor air pollution in hospitality venues in Argentina. Material and Methods. PM2.5 levels were measured in a convenience sample of venues in 15 cities with different legislative contexts following a protocol developed by Roswell Park Cancer Institute. Results. 554 samples were collected. Across all 5 smokefree cities the mean PM2.5 level was lower during daytime vs. evening hours, 24 vs. 98 PM2.5 respectively (p=.012). In the three cities evaluated before and after legislation, PM2.5 levels decreased dramatically (p<0.001 each). Overall, PM2.5 levels were 5 times higher in cities with no legislation vs. smokefree cities (p<0.001). In cities with designated smoking areas, PM2.5 levels were not statistically different between smoking and non-smoking areas (p=0.272). Non-smoking areas had significantly higher PM2.5 levels compared to 100% smokefree venues in the same city (twofold higher) (p=0.017). Conclusions. Most of the participating cities in this study had significantly lower PM2.5 levels after the implementation of 100% smokefree legislation. Hence, it represents a useful tool to promote 100% smokefree policies in Argentina. Objetivo. Evaluar la polución ambiental del sector gastronómico en Argentina. Material y métodos. Se midieron los niveles de partículas respirables (PM2.5) en una muestra por conveniencia de establecimientos de 15 ciudades con diferente legislación, siguiendo un protocolo del Instituto de Cáncer Roswell Park. Resultados. Se recolectaron 554 muestras. En cinco ciudades libres de humo (CLH) la media de PM2.5 durante el día fue baja y menor a la observada durante la noche, 24 vs. 98 PM2.5 respectivamente (p=.012). En las tres ciudades evaluadas antes y después de la legislación, las PM2.5 disminuyeron drásticamente (p<0.001 cada una). Las PM2.5 fueron cinco veces mayores en ciudades sin legislación comparadas con CLH (p<0.001). En ciudades con restricción parcial, no hubo diferencia significativa entre las PM2.5 en el sector fumador y no fumador (p=0.272). Los sectores no fumadores tuvieron niveles PM2.5 significativamente más altos comparados con los lugares 100% libres de humo de la misma ciudad (p= 0.017). Conclusiones. La mayoría de las ciudades participantes en este estudio tuvieron niveles PM2.5 significativamente más bajos tras la implementación de leyes pro ambientes 100% libres de humo de tabaco, por lo que representa una herramienta útil para promover legislación 100% libre de humo en Argentina.